More pace variation and pack formation in successful world-class 10,000-m runners than in less successful competitors - Renfree, A.; Casado, A.; Pellejero, G.; Hanley, B. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To determine different relationships between, and predictive ability of, performance variables at intermediate distances with finishing time in elite male 10,000-m runners. Methods: Official electronic finishing and 100-m split times of the men`s 10,000-m finals at the 2008 and 2016 Olympic Games and IAAF World Championships in 2013 and 2017 were obtained (125 athlete performances in total). Correlations were calculated between finishing times and positions and performance variables related to speed, position, time to the leader, and time to the runner in front at 2000, 4000, 6000, 8000, and 9900 m. Stepwise linear-regression analysis was conducted between finishing times and positions and these variables across the race. One-way analysis of variance was performed to identify differences between intermediate distances. Results: The SD and kurtosis of mean time, skewness of mean time, and position and time difference to the leader were either correlated with or significantly contributed to predictions of finishing time and position at at least one of the analyzed distances (.81 = r = .30 and .001 = P = .03, respectively). These variables also displayed variation across the race (.001 = P = .05). Conclusions: The ability to undertake a high degree of pace variability, mostly characterized by acceleration in the final stages, is strongly associated with achievement of high finishing positions in championship 10,000-m racing. Furthermore, the adoption and maintenance of positions close to the front of the race from the early stages are important to achieve a high finishing position.